Pengujian Dan Penjaminan Kualitas Software Point Of Sale Penjualan Motor PT. XZY Dengan Metode Black Box - Simanjuntak, Antonius; Wijaya, Kurnia Difa; Permatasari, Antini; Astuti, Asri Liya; Zy, Ahmad Turmudi (STIKOM Tunas Bangsa Pematangsiantar, 2024)
The sale of motorcycles at PT.XYZ requires a reliable and high-quality Point of Sale (POS) system to enhance efficiency and customer satisfaction. This research aims to conduct testing and quality assurance of POS software using the Black Box method. This method focuses on testing external functionality without considering the internal system implementation. In this research, testing steps involve identifying the core functionalities of the POS, creating test cases, conducting tests, and analyzing results. Quality assurance will be implemented to ensure that the software meets the specified functional and non-functional requirements